Analysis of the Correlation of MSDS Literacy and Occupational Safety Implementation on Incident Rate Reduction in the Plantation Industry - Wandha Atmaka Aji; Heri Setyawan; subakho aryo saloko; olivia elfatma; indra kurniawan; Bagus Nugroho (Tropical Plantation Journal, 2026)
Work accidents in the industrial sector are a problem that often occurs and has the potential to cause major losses, both in terms of worker safety and company productivity. One of the main factors contributing to the occurrence of accidents is low compliance with chemical handling protocols. In this context, understanding the Material Safety Data Sheet (MSDS) is very important because it serves as the main guide in the safe use, storage, and handling of chemicals.This study aims to analyze the relationship between the level of understanding of MSDS, the effectiveness of implementing procedures in the field, and the number of work accidents. The method used was Pearson correlation analysis involving 40 observational samples. The data obtained showed that the average level of understanding of MSDS was 73.5 and the implementation of procedures in the field was 73.1.The results of the study revealed a very strong negative correlation between the two variables and the number of work accidents, with a coefficient value of -0.938. This shows that the higher the level of understanding and compliance with the MSDS procedure, the lower the number of work accidents. Therefore, increasing education and supervision of the implementation of MSDS is an important step in creating a safer work environment.